The Role of GRI on Financial Performance Phenomenon - Eogenie Lakilaki; Achmad Soediro; Shahir Akram Hassan (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
ntroduction/Main Objectives: This study aims to prove the competence of CSR disclosure usingthe GRI index on the effect of financial performance on the value of Islamic Bank companies inIndonesia. Background Problems: Using FDR, ROA, and CAR as proxies for independentvariables, EVA as a proxy for the dependent variable, GRI as a proxy for moderation variables,and Islamic Commercial Banks in Indonesia. Research Methods: This study uses secondary datain the form of 50 financial statements, which were then processed and analyzed using MRA(Moderation et al.). Finding/Results: The results show that GRI could moderate and strengthenthe effect of Financial Performance both partially and simultaneously on firm value. MaqashidSharia and Islamic Worldview answer the research problem by explaining that after the companymeets its business objectives (maximizing profits). Conclusion: Social goals through CSR practicesas part of Islamic law to increase company value and achieve pleasure.